Histological and three-dimensional evaluation of osseointegration to nanostructured calcium phosphate-coated implants - Jimbo, Ryo; Coelho, Paulo G.; Vandeweghe, Stefan; Schwartz-Filho, Humberto Osvaldo [UNESP]; Hayashi, Mariko; Ono, Daisuke; Andersson, Martin; Wennerberg, Ann (Elsevier B.V., 2011)
Nanostructures on implant surfaces have been shown to enhance osseointegration; however, commonly used evaluation techniques are probably not sufficiently sensitive to fully determine the effects of this process. This study aimed to observe the osseointegration properties of nanostructured calcium phosphate (CaP)-coated implants, by using a combination of three-dimensional imaging and conventional histology. Titanium implants were coated with stable CaP nanoparticles using an immersion technique followed by heat treatment. Uncoated implants were used as the control. After topographical and chemical characterizations, implants were inserted into the rabbit femur. After 2 and 4 weeks, the samples were retrieved for micro-computed tomography and histomorphometric evaluation. Scanning electron microscopy evaluation indicated that the implant surface was modified at the nanoscale by CaP to obtain surface textured with rod-shaped structures. Relative to the control, the bone-to-implant contact for the CaP-coated implant was significantly higher at 4 weeks after the implant surgery. Further, corresponding 3-D images showed active bone formation surrounding the implant. 3-D quantification and 2-D histology demonstrated statistical correlation; moreover, 3-D quantification indicated a statistical decrease in bone density in the non-coated control implant group between 2 and 4 weeks after the surgery. The application of 3-D evaluation further clarified the temporal characteristics and biological reaction of implants in bone. (C) 2011 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Keywords: Nano structures; Micro-CT; Surface chemistry; Bone implant interactions